2016
DOI: 10.15580/gjbs.2016.5.092416145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria in a Study Population in Maiduguri, Nigeria, Symptomatic Manifestations and Public Health Implications

Abstract: on the nature of symptoms observed in patients who were presumptively treated for malaria based on observed symptoms from which analysis was done on the occurrences of each of these symptoms. Then, the prevalence of malaria infection was investigated through data collection at the same hospital. These sets of data collected was centred on patients who attended the hospital (UMTH) between January, 2011 to December, 2011. The age of the patients ranged from 1 to 90 years. Results from questionnaire completed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Seasonal variation in malaria prevalence has been reported in Maiduguri, with the highest prevalence in September, followed by June, and the least prevalence in March [ 68 ]. Seasonal variation has also been reported in the mosquito population and mosquito biting habit in other parts of Nigeria [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variation in malaria prevalence has been reported in Maiduguri, with the highest prevalence in September, followed by June, and the least prevalence in March [ 68 ]. Seasonal variation has also been reported in the mosquito population and mosquito biting habit in other parts of Nigeria [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous interventions had also been effective in increasing malaria preventive practices among the intervention groups [27,49,66,67], the intensity of such interventions in terms of duration, had been contrastingly very high (as some lasted for up to a month) when compared to the single session four-hour intervention in this study. Seasonal variation in malaria prevalence has been reported in Maiduguri, with the highest prevalence in September, followed by June, and the least prevalence in March [68]. Seasonal variation has also been reported in the mosquito population and mosquito biting habit in other parts of Nigeria [69,70].…”
Section: Table 4 Comparison Of Reported Malaria Preventive Practices Between the Groups At Baseline Two Months And Four Months Post-intermentioning
confidence: 96%
“…From the interaction plot between group and time for frequency of ITN use and IPTp uptake, it could be concluded that the intervention was effective in improving the two outcome variables. Seasonal variation in malaria prevalence has been reported in Maiduguri, with the highest prevalence in September, followed by June, and the least prevalence in March [59]. Seasonal variation has also been reported in mosquito population and mosquito biting habit in other parts of Nigeria [60,61].…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of inadequate malaria preventative behaviours among children under the age of five has been observed to be typically low throughout all six geo-political zones in Nigeria. The results of the national malaria situation survey revealed that there is a low prevalence of bed-net usage among the population, as shown by the fact that only 10% of the respondents reported using bed nets (David, et al, 2016). According to the Nigeria Demographics and Health survey conducted in 2018, it was found that a significant portion of the respondents employed various preventative methods.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria has the potential to cause serious and life-threatening consequences in children under the age of five, since their immune systems are still in the process of development and so more susceptible (David et al, 2016). The aforementioned difficulties encompass the presence of severe anaemia, a condition that results in the debilitation of the kid and possesses the potential to pose a threat to their lives if not swiftly addressed.…”
Section: Introductionmentioning
confidence: 99%